Ocular Trauma in a Troubled Zone: Northeastern Nigeria - Askira, B.H.; Waziri, M. A.; Musa, Z. Y. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2016)
Ocular trauma is an important cause of preventable morbidity worldwide, and is a major cause of unilateral visual loss in developing countries. The eye is the third most common organ affected by injuries, after the hands and the feet Objective: We present the pattern of ocular injuries in Maiduguri: An armed conflict area. Material and methods A retrospective study of all the case records of patients with ocular trauma was done between January 2013 and December 2015.Results: Case note of 108 patients were available for this study. There were 86 (66.6%) males and 22(33.3%) females. The age range was between 3 years and 60 years of age. The age range 21 to 30 years was predominant 38 (35.2%). 45 (41.7%) of the patients presented within the first 24 hours. Blast injuries from improvised explosive devises were seen in 54(50.0%), gunshot injuries were seen in 25(23.1 %). 27(25.0%) of the patients had ruptured globe, corneal and corneo-scleral lacerations were seen in 19(17.6%) and 14(13.0%) respectively. Visual acuity on presentation and visual acuity on last visit of 6/18 or better was seen in 32 (31.5%) and 38(35.2%) patients respectively, while 62 (57.4%) and 50 (46.3%)had visual acuity of 3/60 or worst on first presentation and on last visit respectively.Conclusion: The findings from this study highlight a high incidence of severe ocular injury leading to blindness in countries or regions at warA.